Language Variation and Education: Teachers' Perceptions - Haig, Yvonne; Oliver, Rhonda (Language and education, 2003)
Although language variation is widespread and natural, it is subject to judgement. Where a standard language has developed, other varieties tend to be judged against its 'standards'. While a number of overseas studies have found that this type of linguistic bias occurs in education and negatively impacts on dialect speakers, there has been little research in Australia. This research investigates how teachers perceive the speech of school-aged students and whether the socio-economic status or level of schooling of the students influences these perceptions. Altogether 36 teachers from 12 different schools were involved - three teachers from four different schools (n = 12) participating in each of three related but separate studies. The studies used different data collection methods and data were analysed separately and then collated to identify common issues. The findings from this research suggest that teachers' judgement of what is problematic and their perception of what causes these problems may differ according to the socio-economic status of students and to the year level being taught. These findings have important implications for education.